Stakeholders’ perception on implementation of 2008 National Policy on Protection and Assistance to Trafficked Persons in Nigeria - Ibrahim, Sani Sani (2017)
The problem of protection and assistance to trafficked persons has become a serious concern to the Nigerian Government. The country introduced the National Policy on Protection and Assistance to Trafficked Persons in Nigeria 2008 (NPPATPN). However, despite having the policy, the country is still ranked among the countries that do not fully comply with the minimum standard in the prevention of human trafficking and protection of trafficked persons as set by the United States. In addition, the reports from United Nations and National Agency for Prohibition of Traffic in Persons and other Related Matters (NAPTIP) reported that millions of Nigerians are still vulnerable to human trafficking and cases of human trafficking continue to increase. These scenarios raise questions about the actual purpose of the policy, as well as the effectiveness and performance of its implementation. Hence, based on the perspective of policy stakeholders, this study aims to answer: (1) What are the stakeholders’ perception about the purpose of NPPATPN?, (2) What has been the effects of the policy on the lives of trafficked persons?, (3) What factors do the stakeholders perceive to be the obstacles in achieving NPPATPN objectives? The study employed the qualitative method, where semi-structural interviews were conducted with 15 selected informants from four groups of stakeholders. The interview transcripts were analyzed using thematic analysis and have led to three main findings. First, the findings reveal that the policy was designed and formulated as the result of international pressure mounted on the Nigerian government to protect and assist trafficked persons as the strategy to address human trafficking issues from the source countries. Second, the study show that the trafficked persons are not fully protected and assisted with full respect to their human rights, as enshrined in the policy. Third, the finding identifies five main obstacles; lack of freedom to exercise discretion; hierarchical command and control; incomprehensive anti-human trafficking coordination and cooperation; client attitude and cultural belief and; abuse of public trust as the major obstacles to the realization of the NPPATPN. Theoretically, the findings confirm some assumptions of the top-down and bottom-up perspectives of policy implementation theory. The integration of a clear purpose of the policy, coordination of all policy stakeholders and translation of policy into action are crucially important in ensuring effectiveness of policy implementation. The study overall indicates that in the context of the implementation of the NPPATPN, the integration of those aspects are the most critical areas that need to be further examined and evaluated by the government, policymakers and implementers, non-governmental organisations in Nigeria, as well as policy researchers in general. The identified obstacles to the effective protection and assistance to trafficked persons in this study shall provide a basis of understanding the performance of the NPPATPN’s implementation in Nigeria.